Effects of Four Essential Oils on Nutrients Digestibility of In Vitro Ruminal Fermentation - Asih Kurniawati; Widodo Widodo; Wayan Tunas Artama; Lies Mira Yusiati (Buletin Peternakan, 2018)
This research was done to study the effect of four essential oils (EOs), as feed additives, on ruminal nutrient digestibility in order to find out candidate of rumen modifier. Those four EOs were destilated from Foeniculum vulgare (Mill), Pinus merkusii (Jungh. & de Vriese), Cymbopogon nardus (L.) Rendle and Melaleuca leucadendra (L.). Their effect on dry matter (DM), organic matter (OM), crude protein (CP) and crude fiber (CF) digestibility were studied using in vitro rumen fermentation technique according to Theodorou method. Data were statistically analysed using analysis of variance factorial 4x5 design. Feed for fermentation substrate consist of Pennisetum purpureum, rice bran and wheat pollard. Essential oil individually was added and mix with substrate to meet the final concentration in fermentation media of 0, 100, 200, 400 and 800 mg/l. P. merkusii, C. nardus and M. leucadendra EOs reduced DM, OM, and CF digestibilities. The decreasing were in line with the increasing of EOs doses. Therefore F. vulgare only reduced CF digestibility. The value of DM, OM and CP digestibilities in fermentation with F. vulgare did not differ from control. CP digestibility differed among EO treatments. In F. vulgare, and P. merkusii, treatments, CP digestibility did not differ from control, whereas overall CP digestibility in C. nardus tended to be higher than control and CP digestibility in M. leucadendra was significantly higher. All EOs addition reduced CF digestibility at all level. CF digestibility in fermentation added 800 mg/l of M. leucadendra EO was slumped to only 14.29% of control. Among four EOs M. leucadendra is the most potent on interrupt rumen feed fermentation whereas P. merkusii and C. nardus in moderate ways and F. vulgare in delicate manner.